Diagnosis dan Tatalaksana Pneumonitis Hipersensitif - Akbar, Muhammad Rizki; Sangging, Putu Ristyaning Ayu (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Hypersensitive pneumonitis (HP), also known as extrinsic allergic alveolitis, is a complex pulmonary syndrome mediated by the immune system and caused by inhalation of various antigens that have previously been sensitized by the individual. The pathobiology of this disease is not fully understood, but in addition to the triggers that initiate the disease, genetic factors tend to be necessary, because only a small proportion of people are exposed to HP. Because of the lack of standard diagnostic standards, the diagnosis of HP is not directly established and depends on several factors, including the history of exposure, antibodies present in specific antigens, clinical features, bronchoalveolar lavage (LAB), and radiological and pathological features. However, in proper management, high suspicion is significant and can negate the need for more invasive tests. Clinical manifestations and allergic history vary greatly. Corticosteroids may be useful in acute episodes to relieve symptoms or chronic progressive disease, but their long-term effects have never been validated in prospective clinical trials. We conduct a systematic review of published journals about HP. The search uses the Pubmed database using the medical term (MeSH) until January 2020. A total of 13 journals and one textbook were identified.